2019
DOI: 10.1029/2019jg005207
|View full text |Cite
|
Sign up to set email alerts
|

Sea Level Rise Explains Changing Carbon Accumulation Rates in a Salt Marsh Over the Past Two Millennia

Abstract: High rates of carbon burial observed in wetland sediments have garnered attention as a potential “natural fix” to reduce the concentration of carbon dioxide (CO2) in Earth's atmosphere. A carbon accumulation rate (CAR) can be determined through various methods that integrate a carbon stock over different time periods, ranging from decades to millennia. Our goal was to assess how CAR changed over the lifespan of a salt marsh. We applied a geochronology to a series of salt marsh cores using both 14C and 210Pb ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…The signature of δ 13 C and its relation with C/N is similar in sediments and groundwater samples, indicating that groundwater obtains most of its carbon from soils, exporting later to the ocean. Our carbon burial rates (62 ± 32 g m −2 year −1 ) were 37% of the global average for salt marsh ecosystems (168 ± 7 g m −2 year −1 ; Wang et al 2021) but similar to rates reported in other studies in the USA (60 g m −2 year −1 ; Chmura et al 2003;Mctigue et al 2019;Wang et al 2019). Comparing carbon burial in the marsh and groundwater exports represents a challenge because these processes were quantified at different time scales.…”
Section: Carbon Burial and Origins Of The Exported Carbonsupporting
confidence: 84%
“…The signature of δ 13 C and its relation with C/N is similar in sediments and groundwater samples, indicating that groundwater obtains most of its carbon from soils, exporting later to the ocean. Our carbon burial rates (62 ± 32 g m −2 year −1 ) were 37% of the global average for salt marsh ecosystems (168 ± 7 g m −2 year −1 ; Wang et al 2021) but similar to rates reported in other studies in the USA (60 g m −2 year −1 ; Chmura et al 2003;Mctigue et al 2019;Wang et al 2019). Comparing carbon burial in the marsh and groundwater exports represents a challenge because these processes were quantified at different time scales.…”
Section: Carbon Burial and Origins Of The Exported Carbonsupporting
confidence: 84%
“…The FC sites were within an extensive S. alterniflora –dominated marsh, while the TBC site was within a S. alterniflora zone that transitioned into Juncus roemerianius (Davis et al, 2017; McTigue et al, 2019). The tidal range averaged 0.31 m at TBC and 0.83 m at FC (Lettrich, 2011; McTigue et al, 2019). Seasonal differences in water level were greater at TBC than FC, due to the influence of freshwater inputs and wind‐driven tides (Ensign et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A third site was selected in the interior of a fringing marsh near the mouth of Traps Bay Creek (TBC), a tidal creek in an embayment within the New River Estuary. The FC sites were within an extensive S. alterniflora -dominated marsh, while the TBC site was within a S. alterniflora zone that transitioned into Juncus roemerianius (Davis et al, 2017;McTigue et al, 2019). The tidal range averaged 0.31 m at TBC and 0.83 m at FC (Lettrich, 2011;McTigue et al, 2019).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The CAR measured in 59 Atlantic coast salt marsh sites averaged 126 ± 87 g C m −2 year −1 (Ouyang & Lee, 2014), similar in magnitude to the 83.5 g C m −2 year −1 NECB estimated in FC interior control plots. Traps Bay, a marsh within the New River Estuary several miles from FC, was found to have a CAR rate of 167 g C m −2 year −1 over a 4-year time scale (McTigue et al, 2019). However, CAR is measured using wide variety of methods and interpretations that are difficult to capture with a broad brush.…”
Section: Net Ecosystem Carbon Balancementioning
confidence: 99%